Business Innovation as the Key to Sustainability and Competitiveness at the PT Yamaha Music Manufacturing Asia Cooperative - Santi Rimadias (Aksi Kita: Jurnal Pengabdian kepada Masyarakat, 2026)
Cooperatives face various challenges in maintaining sustainability and competitiveness due to technological developments, changing member needs, and increasing business competition. These conditions require cooperatives to be able to develop business innovation as a strategy to improve service quality and added value for members. This community service activity was packaged in the form of training, aimed at increasing the understanding of the management and members of the PT Yamaha Music Manufacturing Asia Cooperative regarding the concept of business innovation and encouraging their ability to identify and design innovations that suit the needs of the cooperative. The activity was carried out on November 15, 2025, through a participatory approach that combined lectures, interactive discussions, case studies, group simulations, reflections, and question-and-answer sessions. Evaluation was carried out through observations of participant participation, discussion results, and innovation ideas generated during the activity. The results of the community service showed an increase in participants' understanding of the concept of business innovation, the difference between invention and innovation, and various forms of innovation that can be applied to cooperatives. Participants were also able to identify factors that drive and hinder innovation and formulate various realistic innovative ideas, such as digitizing member services, developing cooperative products, and utilizing social media as a marketing tool. This activity had a positive impact on increasing knowledge, changing attitudes that are more open to innovation, and the ability of participants to develop alternative solutions for cooperative development. Therefore, business innovation training needs to be continued through mentoring programs so that the innovative ideas that have been formulated can be implemented sustainably.